Acceptor Comment of PostPlacental Copper T380A Intrauterine Device - Eka R Gunardi; Adila RA Malik; Febby Oktavianti; Riry Meria,; Fachreza Ardianto; Christina Marian (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To describe the characteristics of subjective complaints reported by post-placental inserted intrauterine device (IUD) acceptor, especially those who used Copper T380A (CU T380A) type of IUD. Methods: Seventy-two-married women whose age ranged from 19 to 44 years old and received post-placental IUD in Dr. Cipto Mangunkusumo Hospital, Jakarta, were included in this study. Subjective complaints regarding the use of CU T380A IUD were evaluated twice including during the puerperium and six months afterwards by a direct interview. Results: Most respondents were 20-35 years old, 50% of whom were primiparous (n=36). There were 42% respondents reporting pain during insertion, 32% respondents reporting abdominal pain during the use, 22% respondents reporting menstrual disorder, 18% respondents reporting vaginal discharge, and 3% respondents complaining of having IUD repulsion. Conclusion: There are variety of subjective complaints reported after post-placental IUD use. However, most of the respondents does not complain anything. [Indones J Obstet Gynecol 2017; 5-1: 19-22] Keywords: complication, contraception, intrauterine device (IUD) post-placental, postpartum